Transcriptomic analysis of genes associated with vitamin D receptor signalling reveals differences between skin cancers - Ocanha-Xavier, Juliana Polizel [UNESP]; Xavier-Junior, José Cândido Caldeira [UNESP]; Miot, Hélio Amante [UNESP]; da Silva, Márcia Guimarães [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Wiley, 2024)
Vitamin D activates the vitamin D receptor (VDR), which dimerizes preferentially with the retinoid X receptor-α (RXRα). This heterodimer connects with genetic elements responsive to vitamin D, inhibiting or stimulating gene activity. We performed Nanostring® analysis of VDR/RXRα to compare the mRNA expression of this heterodimer and their correlated transcriptomes in non-melanoma skin cancer (basal cell carcinomas (BCC) and squamous cell carcinomas (SCC)) and melanocytic lesions (intradermal nevi (IN), and melanomas (MM)) with control skin. To evaluate VDR, RXRα and other 22 correlated genes in BCC, SCC, IN and MM, paraffin samples had their transcriptomes analysed using Nanostring®, a platform that allows multiple mRNA analyses. There were 46 samples, including 11 BCC, 10 SCC, 10 IN, 12 MM and 3 pools of control skins. Most mRNAs differed between the lesion groups and the control group. BCC and SCC NCOR2 were upregulated; in MM and IN, RXRγ was higher than in the control group. TP53, FOXO3 and MED1 showed a significant difference when we compared the BCC group to the SCC group. Melanoma and intradermal nevi differed only in AhR. VDR and RXRα were lower than the control in all groups. The panel shows a clear difference between the non-melanocytic cancers and, on the other hand, a slight difference between the melanocytic lesions. The study of vitamin D's influence through its receptor and RXRα is an exciting issue for understanding the importance of this pathway, and the present study can impact the prevention and treatment strategies, mainly in non-melanocytic tumours.
Keywords: calcitriol; carcinoma, squamous cell; melanoma; retinoid X receptor alpha; VDR